Pengaruh Pengeluaran Zakat Perbankan, Ukuran Perusahaan dan Islamic Social Responsibility (ISR)Terhadap Profitabilitas pada Bank Umum Syariah di Indonesia Periode 2016-2019 - Eliana Eliana; Intan Novia Astuti; Nurbismi Nurbismi; Akmal Riza (Jurnal EMT KITA, 2020)
This study aims to see the effect of banking zakat expenditure, company size and Islamic Social Responsibility on profitability. The data of this research uses the financial report data Annual Report or the annual report of each Islamic Commercial Bank for the period 2016-2019. This study uses a quantitative research approach with data analysis methods using multiple linear regression models. Hypothesis testing is done by statistical tests, namely partial test (t-test) and simultaneous test (F-test) with a significance level of 5%. Simultaneous test results show that banking zakat expenditure, company size and ISR simultaneously have a positive and significant effect on profitability. Partially, the bank zakat expenditure variable has a positive and significant impact on profitability, while the company size variable and ISR have no effect on profitability at Islamic Commercial Banks.